The Unknown Satanic Verses Controversy on Race and Religion - Daglier, Üner (Politics, literature, & film., 2020)
Decades after its publication, Salman Rushdie's controversial novel The Satanic Verses remains much talked about and little understood. The Unknown Satanic Verses Controversy on Race and Religion now responds to this critical gap through painstakingly detailed attention to the totality of Rushdie's text.